Camrelizumab-based therapies for the treatment of advanced lung cancer: a prospective, open-label, multicenter, observational, real-world study - Zhao, Dong; Bi, Minghong; Cheng, Xiaofei; Wang, Shuhong; Cheng, Huaidong; Xia, Xiaoyang; Chen, Huan; Zhang, Yanbei; Hu, Zhiqiang; Cao, Qisheng; Liang, Hui; Wang, Fan; et al. (Frontiers in Immunology, 2025)
ObjectiveCamrelizumab, a programmed death-1 inhibitor, is effective and safe for treating patients with advanced lung cancer according to previous phase 3 trials. However, relevant real-world clinical evidence is required. This study intended to explore the efficacy and safety of camrelizumab-based therapies in patients with advanced lung cancer.MethodsPatients with advanced lung cancer who received camrelizumab-based therapies as first-line or above treatment were consecutively enrolled in this study. The median follow-up duration was 5 months.ResultsA total of 298 subjects were enrolled. Objective response rate (ORR) and disease control rate (DCR) were 27.2% and 82.2%. Multivariable logistic regression analysis showed that previous pulmonary surgery [odds ratio (OR)=0.440, P=0.024], previous radiotherapy (OR=0.410, P=0.010), and Eastern Cooperative Oncology Group Performance Status (ECOG PS) score (>1 vs. 0 1) (OR=0.414, P=0.046) were independently and negatively associated with ORR. The median progression-free survival (PFS) [95% confidence interval] was 10.0 (7.8-12.2) months. Median overall survival (OS) was not reached. Multivariable Cox regression analysis suggested that brain metastasis [hazard ratio (HR)=1.548, P=0.036] and liver metastasis (HR=1.733, P=0.035) were independently associated with shorter PFS. Previous chemotherapy (HR=2.376, P=0.022), brain metastasis (HR=2.688, P=0.006), and liver metastasis (HR=2.583, P=0.039) were independently associated with shorter OS. Most adverse events were grade I or II. Grade III and IV adverse events rarely occurred. The occurrence of adverse events was associated with a higher DCR (P=0.003).ConclusionsCamrelizumab-based therapies may serve as potential treatments for patients with advanced lung cancer. However, further studies with an extended follow-up duration are warranted.